ANALISIS PENGARUH PERUBAHAN TUTUPAN LAHAN TERHADAP HIDROLISIS DAS PAMUKKULU SULAWESI SELATAN - Andi Rasti Serastiwati; St. Subaedah; Netty Syam (Percetakan Umi Toaha Makassar, 2020)
The Pamukkulu watershed is one of the Jeneberang-Kelara Sub-watersheds, which is one of the 108 Priority Watersheds in Indonesia determined based on the 2017 Ministry of Environment and Forestry Performance Report which is prioritized as a location for Forest and Land Rehabilitation activities. The purpose of this study was to analyze changes in land cover in the Pamukkulu watershed in 2008 and 2017, the effect of land cover changes in the Pamukkulu watershed on fluctuations in major river flows and analyze the health level of the Pamukkulu watershed based on analysis of major river discharge and changes in land cover. The study was conducted in February to April 2018. Data collection was carried out by taking secondary data in the form of land cover data in 2008 and 2017, climate data and Pamukkulu River discharge data. The results showed that based on the results of the analysis of the Land Cover Index (IPL), the condition of Pamukkulu watershed land cover in 2008 was at 19.38% and 16.96% in 2017 so that it was categorized as bad. The results of the hydrological analysis (river water discharge) on the River Regime Coefficient in 2008 were 125 and in 2017 amounted to 119.6 so that the KRS is also categorized as bad. While the results of the analysis of the Variant Coefficient (CV) in 2008 amounted to 144.90% and in 2017 amounted to 87.5% then the CV was categorized as poor. Based on the analysis of the value of the Land Cover Index, River Regime Coefficient and River Regime Coefficient in the Pamukkulu Watershed in 2008 and 2017 which are in the poor category, the performance of the Pamukkulu Watershed is in the poor category.